Math is easy 4.0 / Norlida Othman ... [et al.]. - Othman, Norlida; Mohamed, Nadiah; Yaacob, Nurul Aityqah; Mohd Ruslan, Siti Zaharah; Andu, Yusrina; Ismail, Norul Fadhilah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The Math is Easy 4.0 workshop was held by the College of Computing, Informatics, and Mathematics at UiTM Cawangan Negeri Sembilan, Kampus Kuala Pilah, from January 20 to January 24, 2024. This one-week event aimed to enhance students' mathematical skills through interactive learning sessions. Targeting pre-diploma and diploma students, the workshop focused on essential areas such as problem-solving, critical thinking, and the practical applications of mathematical concepts. This program is available in both in-person and online formats. Through this comprehensive workshop, students developed the skills and strategies necessary to effectively tackle exams and achieve their academic goals.